AN ANALSYSIS REALITY OF GENDER INEQUETY WOMEN BALI IN THE NOVEL “TEMPURUNG” BY OKA RUSMINI - Yayu Wahyuni Hidayat; Tuti Kartika; Enung Nurhayati (IKIP Siliwangi, 2020)
One point of view of the study of literary feminism is describing the forms of gender injustice that afflict female leaders. In this case, Sara Mills looks at the position of the figures displayed and focuses on how the readers and writers are in the text. Factors that led to gender injustice towards Balinese female figures, as well as forms of resistance to gender injustice carried out by Balinese female figures in the novel Tempurung by Oka Rusmini. This paper is a qualitative descriptive form. The subject of this analysis is the Tempurung novel by Oka Rusmini. Discourse analysis focused on gender injustice that afflicted Balinese female figures studied using biographical criticism and historical feminist literature. Data is obtained from reading techniques and note taking techniques. Data is analyzed through qualitative descriptive analysis techniques. The results showed: (1) The position of the subject-objects from the characterization of the novel